Effect of Ishige okamurae extract on musculoskeletal biomarkers in adults with relative sarcopenia: Study protocol for a randomized double-blind placebo-controlled trial - Lee, Sae Rom; Lee, Ye Li; Lee, Sang Yeoup (Frontiers in Nutrition, 2022)
Introduction: Sarcopenia is a phenomenon in which skeletal muscle mass decreases with age, causing many health problems. Many studies have been conducted to improve sarcopenia nutritionally. Ishige okamurae (IO) is a genus of brown algae, and plays a role in anti-diabetes, anti-obesity, and myogenesis. However, the effect of IO extract (IOE) on human muscle strength and mass is unclear. Therefore, we tested the effect and safety of consumption of IOE for 12 weeks on muscle strength and mass in middle-aged and old-aged adults with relatively low skeletal muscle mass. Materials and Methods: A randomized controlled trial is conducted on 80 adults aged 50-80. A total of 80 participants will be enrolled in this study. Participants assign IOE-taking group (n=40) and placebo taking group (n=40). At a baseline and 12 weeks after treatment, the following parameters of the participants are checked: knee extension strength, handgrip strength, body composition, laboratory tests, dietary recall, physical activity, and EQ-5D-5L. Discussion: The present study will be the first randomized, double-blind placebo-controlled trial to examine the efficacy and tolerability of IOE supplementation in adults with relatively low muscle mass. The nutritional intake and physical activity that might influence muscle strength and mass will be considered as covariates for transparency of results. The results of this study will provide clinical evidence for sarcopenia patients with nutrient treatment. Clinical Trial Registration: www.clinicaltrials.gov/, Identifier: NCT04617951.